The problem with growing corporate concentration and power in the global food system - Jennifer Clapp (Nature Food, 2021)
What are the potential consequences when a relatively small number of large firms come to dominate markets within the global food system? This Perspective examines the implications of corporate concentration and power in the global seed and agrochemical industry, a sector that has become more consolidated in recent years. It outlines the pathways via which concentrated firms in this sector have the potential to exert power in food systems more broadly—both directly and indirectly—in ways that matter for food system outcomes. Specifically, concentrated firms can shape markets, shape technology and innovation agendas, and shape policy and governance frameworks. This Perspective makes the case that a range of measures are needed to ensure that corporate concentration and power do not undermine key goals for food systems, such as equitable livelihoods, sustainability and broad-based participation in food system governance. These include measures to strengthen competition policies, to bolster public sector support for diverse food systems, and to curb corporate influence in the policy process.